Transient liquid phase bonding using Ni/Sn multilayers for high temperature applications - Melvin (2014)
With growing demand in electronic system for operating in harsh conditions makes the idea of research focus more on a reliable and resilient packaging of the interconnect components. The components of these devices are subjected to wide range of temperatures therefore the reliability and resilience of the components must be sufficient to produce a device with an acceptable lifetime. Some conventional solder joints have been experimented but they were proven to have a lower melting point than the service temperature, making them become inappropriate candidates for high-temperature applications. Consequently, a new bonding method which incorporated both dissolution bonding and diffusion bonding i.e. Transient Liquid Phase (TLP) bonding is developed for addressing this issue. Moreover, its benefits to produce high quality bond at lower processing temperature has made this method as a prominent method particularly for bonding metallurgical systems.